2009
DOI: 10.1177/1933719108327592
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Progesterone Treatment Rescues the Mammary Impairment Following Uteroplacental Insufficiency and Improves Postnatal Pup Growth in the Rat

Abstract: Uteroplacental insufficiency in the rat reduces maternal progesterone and impairs mammary function and pup milk intake, compromising postnatal growth. We determined whether progesterone administration to rat dams progesterone-deficient following uteroplacental insufficiency improves lactation and pup growth. Uteroplacental insufficiency (Restriction) or sham surgery (Control) was performed on day 18 of pregnancy in WKY rats. Pregnant dams were injected with progesterone or vehicle, and Control mothers with veh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 38 publications
(62 reference statements)
0
10
0
Order By: Relevance
“…Total calcium concentrations were determined using colorimetric spectrometry using the Synchron CX‐5 Clinical System (Beckman Coulter; Lane Cove, NSW, Australia) and ionic calcium (active or free calcium; regulated by PTHrP), sodium and potassium concentrations were determined using ion selective electrodes correcting for pH (Ciba‐Corning model 644; Cambridge, MA, USA) from milk as well as from pup and maternal plasma (Wlodek et al . , ). Total calcium concentration in the pup body was determined after ashing using the CX‐5 Analyser (Wlodek et al .…”
Section: Methodsmentioning
confidence: 99%
“…Total calcium concentrations were determined using colorimetric spectrometry using the Synchron CX‐5 Clinical System (Beckman Coulter; Lane Cove, NSW, Australia) and ionic calcium (active or free calcium; regulated by PTHrP), sodium and potassium concentrations were determined using ion selective electrodes correcting for pH (Ciba‐Corning model 644; Cambridge, MA, USA) from milk as well as from pup and maternal plasma (Wlodek et al . , ). Total calcium concentration in the pup body was determined after ashing using the CX‐5 Analyser (Wlodek et al .…”
Section: Methodsmentioning
confidence: 99%
“…Progesterone withdrawal at the end of pregnancy is necessary to initiate lactation (37,28), and suckling-induced prolactin (2) and oxytocin (5) release, in combination with milk removal, are responsible for the maintenance of lactation. In the rat, uteroplacental insufficiency has been shown to induce premature withdrawal of progesterone in late gestation, thereby stimulating early onset milk production (55). In our model of low-to-moderate EtOH consumption, circulating levels of progesterone and prolactin were unaltered, suggesting that the initiation and maintenance of lactation was not disrupted by EtOH.…”
Section: Discussionmentioning
confidence: 63%
“…Secretory differentiation of the mammary gland can be altered by a number of insults. Animal models have shown that secretory differentiation is disrupted by maternal: uteroplacental insufficiency (55), undernutrition (46), obesity (17), hypertension (56), and vitamin A deficiency (8). Most of these insults result in decreased mammary alveolar development.…”
mentioning
confidence: 99%
“…Prenatal maternal insults can affect postnatal rearing and/or lactation resulting in poor postnatal weight gain of neonates [23, 23, 46, 47]. Mothers that have uteroplacental insufficiency, created by prenatal ligation of the uterine artery on day 18 of gestation, produce less milk with altered composition, including less calcium, compared to control rats [23].…”
Section: Discussionmentioning
confidence: 99%